2005
DOI: 10.1002/bit.20345
|View full text |Cite
|
Sign up to set email alerts
|

Novel approach to quantify immobilized‐enzyme distributions

Abstract: The quantitative intraparticle enzyme distribution of Assemblase, an industrially employed polydisperse immobilized penicillin-G acylase, was measured. Because of strong autofluorescence of the carrier, the generally applied technique of confocal scanning microscopy could not be used; light microscopy was our method of choice. To do so, Assemblase particles of various sizes were sectioned, labeled with antibodies specifically against the enzyme, and analyzed light microscopically. Image analysis software was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…A higher enzyme concentration close to the surface could also explain why the measured substrate concentrations close to the interface are lower than those predicted by the kinetic model. Higher enzyme concentrations close to the interface were observed for gelatin-chitosan particles (Assemblase ®) (van Roon et al, 2005) or for alginate hydrogel beads at low protein loadings (Heinemann, 2003). Therefore, the assumption of a homogeneous distribution of the enzymes within the κ-carrageenan hydrogel bead should be investigated in further studies.…”
Section: Resultsmentioning
confidence: 99%
“…A higher enzyme concentration close to the surface could also explain why the measured substrate concentrations close to the interface are lower than those predicted by the kinetic model. Higher enzyme concentrations close to the interface were observed for gelatin-chitosan particles (Assemblase ®) (van Roon et al, 2005) or for alginate hydrogel beads at low protein loadings (Heinemann, 2003). Therefore, the assumption of a homogeneous distribution of the enzymes within the κ-carrageenan hydrogel bead should be investigated in further studies.…”
Section: Resultsmentioning
confidence: 99%
“…[57] This latter conclusion has recently been confirmed by immunolabeling. [58] The performance of Assemblase in the synthesis of cephalexin from (R)-phenylglycine amide and 7-ADCA (see Figure 3) was investigated in detail and compared with dissolved enzyme. [59] Assemblase was a less efficient acyl transfer catalyst, as judged by the S/H ratio [23] , than the dissolved enzyme, which is ascribed to diffusion limitation in the Assemblase carrier.…”
Section: Gelatin-chitosanmentioning
confidence: 99%
“…With the enzyme in Assemblase predominantly situated in the outer regions of the particle (Van Roon et al 2005a), the yield and selectivity are better than that of a particle with a homogeneous enzyme distribution and much better than one with an active core ( Table 2). This results from an improved supply of 7-ADCA to the enzyme and the reduced secondary hydrolysis of the 'slow' CEX for the case of Assemblase.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme loading and distribution were previously measured for multiple particle sizes (Van Roon et al 2005a). It was shown that all size-dependent intraparticle enzyme distributions within Assemblase had the mathematical shape of in-stationary enzyme penetration profiles and could be described with a Fourier number as a function of the particle radius.…”
Section: Enzyme Loading and Enzyme Distributionmentioning
confidence: 99%
See 1 more Smart Citation